Copper-induced activation of TRP channels promotes extracellular calcium entry, activation of CaMs and CDPKs, copper entry and membrane depolarization in Ulva compressa - Gómez, Melissa; González, Alberto; Sáez, Claudio A.; Morales, Bernardo; Moenne, Alejandra (Frontiers in Plant Science, 2015)
In order to identify channels involved in membrane depolarization, Ulva compressa was incubated with agonists of TRP channels C5, A1 and V1, and the level of intracellular calcium was detected. Agonists of TRPC5, A1 and V1 induced increases in intracellular calcium at 4, 9, and 11 min of exposure, respectively, and antagonists of TRPC5, A1, and V1 corresponding to SKF-96365 (SKF), HC-030031 (HC), and capsazepin (CPZ), respectively, inhibited calcium increases indicating that functional TRPs exist in U. compressa. In addition, copper excess induced increases in intracellular calcium at 4, 9, and 12 min which were inhibited by SKF, HC, and CPZ, respectively, indicating that copper activate TRPC5, A1, and V1 channels. Moreover, copper-induced calcium increases were inhibited by EGTA, a non-permeable calcium chelating agent, but not by thapsigargin, an inhibitor of endoplasmic reticulum (ER) calcium ATPase, indicating that activation of TRPs leads to extracellular calcium entry. Furthermore, copper-induced calcium increases were not inhibited by W-7, an inhibitor of CaMs, and staurosporine, an inhibitor of CDPKs, indicating that extracellular calcium entry did not require activation of CaMs and CDPKs. In addition, copper induced membrane depolarization events at 4, 8, and 11 min and these events were inhibited by SKF, HC, CPZ, and bathocuproine, a specific copper chelating agent, indicating that copper entry through TRP channels leads to membrane depolarization. Moreover, membrane depolarization events were inhibited by W-7 and staurosporine, indicating that activation of CaMs and CDPKs is required to allow copper entry through TRPs. Interestingly, copper-induced calcium increases and depolarization events were light-dependent and were inhibited by DCMU, an inhibitor of photosystem II, and ATP-γ-S, a non-hydrolizable analog of ATP, suggesting that ATP derived from photosynthesis is required to activate TRPs. Thus, light-dependent copper-induced activation TRPC5, A1 and V1 promotes extracellular calcium entry leading to activation of CaMs and CDPKs which, in turn, promotes copper entry through TRP channels and membrane depolarization.